2015
DOI: 10.2147/dddt.s84982
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic indeno[1,2-b]indoles as ABCG2-selective potent and non-toxic inhibitors stimulating basal ATPase activity

Abstract: Ketonic indeno[1,2-b]indole-9,10-dione derivatives, initially designed as human casein kinase II (CK2) inhibitors, were recently shown to be converted into efficient inhibitors of drug efflux by the breast cancer resistance protein ABCG2 upon suited substitutions including a N5-phenethyl on C-ring and hydrophobic groups on D-ring. A series of ten phenolic and seven p-quinonic derivatives were synthesized and screened for inhibition of both CK2 and ABCG2 activities. The best phenolic inhibitors were about three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…During the last few years we have identified certain classes of compounds as potent ABCG2 inhibitors, including chromones 15 , 16 , stilbenes 17 , chalcones 18 and indeno[1,2- b ]indoles 19 , 20 . Designed initially as casein kinase II (CK2) inhibitors, the indeno[1,2- b ]indole derivatives seem to be the most promising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years we have identified certain classes of compounds as potent ABCG2 inhibitors, including chromones 15 , 16 , stilbenes 17 , chalcones 18 and indeno[1,2- b ]indoles 19 , 20 . Designed initially as casein kinase II (CK2) inhibitors, the indeno[1,2- b ]indole derivatives seem to be the most promising.…”
Section: Introductionmentioning
confidence: 99%
“…Designed initially as casein kinase II (CK2) inhibitors, the indeno[1,2- b ]indole derivatives seem to be the most promising. Previously, we showed that indeno[1,2- b ]indole derivatives that inhibit CK2 can be successfully converted into potent ABCG2 inhibitors 19 , 20 . In this study, further structural insights on rings A, B and D led us to synthesize new indeno[1,2- b ]indole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested interesting off-target effects with multi-drug resistance transport systems typically induced under cytotoxic conditions. This feature, further the flat and extended hydrophobic scaffold that resembled ATP-competitive CK2 inhibitors [ 41 ], and finally the plethora of functionalization opportunities provided by a tetracyclic ring system inspired ideas to use the indeno[1,2- b ]indole framework as the basis for polypharma-cology approaches: first Hundsdörfer et al [ 50 , 51 ] described a collection of indeno[1,2- b ]indole-type CK2 inhibitors all of them equipped with an oxo group at position 10 ( Figure 1 c–e) and the best of them with an attractive selectivity profile against a panel of 22 EPKs; later Gozzi et al [ 52 , 53 ] demonstrated how this indeno[1,2- b ]indole-10-one scaffold can be further derivatized at the rings A, C and D in different ways in order to create inhibitors targeting selectively either CK2 or the breast cancer resistance protein ABCG2—an ABC half transporter overexpressed in breast cancer cells [ 54 ]; and finally Alchab et al [ 55 ] extended this differentiation to a third cancer-relevant enzyme target, namely the cell cycle key phosphatase CDC25. In summary, with respect to the target CK2 about 50 indeno[1,2- b ]indole-based inhibitor candidates were described which have been recently clustered according to their D-ring substitution into a quinonic ( Figure 1 c), a phenolic ( Figure 1 d) and a ketonic ( Figure 1 e) subgroup [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…On this regard, it is worth to mention that CK2 inhibitors have been derivatized for targeting both CK2 and the breast cancer resistance protein ABCG2 [61]. The same group found that the structure-activity relationships for CK2 and ABCG2 are totally different, and they developed compounds blocking the extrusion pump without significantly inhibiting CK2 [62]; however, a dual CK2/ABCG2 inhibitor is particularly interesting, considering that co-administration of pump-inhibitors and cytotoxic agents is one of the strategies proposed to fight MDR [13].…”
Section: Main Textmentioning
confidence: 99%
“…In the context of this paragraph on CK2 inhibitors, it might be interesting reminding that some of them have been derivatized to simultaneously target different molecules, as in the case of Cx-platin, a CK2 targeting Pt-based drug, able to reverse cisplatin resistance by causing DNA damage and inhibiting CK2-mediated DNA repair activity [31]. Moreover, the possibility exists for the development of molecules targeting CK2 and extrusion pump of the ABC protein family [61, 62]. Finally, although not pertinent to cancer, we would like to mention that, to counteract bacteria resistance to aminoglycoside antibiotics, CK2 inhibitors have been proposed as a structural base to design nucleotide-competitive inhibitors against aminoglycoside O-transferases [128].…”
Section: Main Textmentioning
confidence: 99%